2009
DOI: 10.1089/thy.2008.0230
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm of the Inferior Thyroid Artery Presenting as a Thyroid Nodule

Abstract: A 63-year-old woman complained of a growing neck mass. Sonography revealed a solid and cystic mass in the right thyroid lobe. Color Doppler study and computed tomography revealed anechoic cystic portions within the thyroid nodule to be a pseudoaneurysm arising from the right inferior thyroid artery. The only identifiable risk factor was a past thyroid needle biopsy performed approximately 5 years previously according to the patient's recollection. Right lobectomy was performed and the pseudoaneurysm was treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…In such a situation, an early and accurate diagnosis is essential. Our case, and three other case reports (3)(4)(5) describing the diagnosis of active bleeding into the thyroid gland, show the capability of modern imaging techniques to diagnose active bleeding into the thyroid gland preoperatively.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…In such a situation, an early and accurate diagnosis is essential. Our case, and three other case reports (3)(4)(5) describing the diagnosis of active bleeding into the thyroid gland, show the capability of modern imaging techniques to diagnose active bleeding into the thyroid gland preoperatively.…”
Section: Resultssupporting
confidence: 57%
“…It can demonstrate hematomas and abscess formation, among others. It has been reported that ultrasound with Doppler technique is capable of diagnosing active bleeding or pseudoaneurysm (3)(4)(5). A CT scan is usually used in these situations in cases with discrepancies between ultrasound and clinical findings, or in those with unclear clinical symptoms.…”
Section: Active Bleeding Into the Thyroid Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, only four cases were treated by coil embolization alone4,5,9,10). Various clinical manifestations of these aneurysms have been reported, including palpable neck mass, hoarseness, dysphagia, respiratory distress, or evaluation of a possible thyroid nodule1,8,12,14).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no absolute evidence of a true aneurysm like pre-procedural image or pathologic specimen in this case. There were several reports about iatrogenic aneurysm near thyroid gland, following vascular catheterization2), percutanous needle biopsy of adjacent organ8) and radiotherapy3). There was also a case report of tracheostomy-related pseudoaneurysm that developed in superior thyroid artery11).…”
Section: Discussionmentioning
confidence: 99%